Analysis of the effect of website quality on user satisfaction based methods WebQual the state university website surabaya - Pramudya Wikrama; Sulistiowati Sulistiowati; Agus Dwi Churniawan (Jurnal Sistem Informasi Universitas Dinamika, 2017)
The website is one of campaign media to attract users to join it. Therefore,the state University of Surabaya utilize the website for the promotion of University and should know exacth its satisfaction in order to achieve the objectives of promotion. on this basis there should be research using quantitative descriptive type involving 95 respondents focused on methods of quality website (website quality) 4.0 by using SPSS version 21.The results stated that the quality dimension in the form of website usability, information quality and interaction quality positively affect users satisfaction. keywoeds: website quality,users satisfaction,state University of Surabaya